Utilization of Keystone Flaps in High Voltage Electrical Burns (Medical Forum Monthly, 2024)
Objective: This study aims to describe the use of Keystone flaps in patients with high voltage electrical injuries where local flaps were a possibility.Study Design: Descriptive / analytic study.Place and Duration of Study: This study was conducted at the Bolan Medical Complex Hospital and Jilani Hospital Quetta, Pakistan from April 2013 to August 2015Materials and Methods: A total of ten patients with eleven high voltage electrical injury wounds reconstructed with keystone flaps were identified. Variables noted were patient demographics, comorbid conditions, size and location of defect, type of keystone flap used, and complications noted. SPSS 14 was used to note the variables. No statistical test applies to this study.Results: Eleven defects in ten patients were reconstructed with Keystone flaps. Eight of the defects were on lower extremity, two on upper extremity and one on abdomen. The most commonly employed flap was Type IV keystone flap in six patients, Type II A in two patients, Type III in one and Type II B in one patient. No total flap failures were noted. One flap suffered distal one cm flap loss but after debridement, direct closure was obtained. Two patients had wound dehiscence requiring resuturing.Conclusion: This case series demonstrated the safety, reliability and applicability of Keystone flaps in selected defects secondary to high voltage electrical injury.